An Optimal Tone Mapping Technique with Random Phase Sequence Matrix for PAPR Reduction in Wireless OFDM Systems - Santhosh, Sheeba; Aloy Anuja, G. (International Journal of Engineering and Technology, 2018)
Orthogonal frequency division multiplexing (OFDM) is most popular technique Â for wireless multimedia communication due to its extraordinary property that makes it reliable in frequency-selective fading conditions. Despite of its popularity OFDM faces Â some challenging issues which is difficult to solve. One such issue is peak to average power ratio (PAPR).this paper proposes an optimal tone mapping technique that employs a random phase sequence matrix for complex less PAPR reduction (OTM-PAPR). It works on pre- coding the message symbol constellation using tone mapping . Initially multiplication of phase rotation factor is done and inverse fast fourier transform is done. The optimal tone mapping is achieved by an improved multi-objective fish swarm optimization (IMFSO) algorithm. Here, an OFDM system is implemented using quadrature phase shift keying modulation technique in MATLAB software. The results show that the performance of proposed OTM-PAPR technique is very efficient in terms of PAPR value and computational complexity reduction ratio.Â